Robust Trend Estimation for AR(1) Disturbances - Roland Fried; Ursula Gather (Austrian Journal of Statistics, 2016)
We discuss the robust estimation of a linear trend if the noise follows an autoregressive process of first order. We find the ordinary repeated median to perform well except for negative correlations. In this case it can be improved by a Prais-Winsten transformation using a robust autocorrelation estimator.